Assessment of nitric oxide and peroxiredoxin along with frap in newly diagnosed patients of type 2 diabetes mellitus - Kidwai, Mohd Zaid; Bindra, Maninder (Health Sciences International Journal, 2024)
Background: The pathophysiological mechanisms underlying Type 2 Diabetes Mellitus (T2DM) involves oxidative stress and impaired antioxidant defense systems. Objective: Hence, we aimed to assess Nitric Oxide (NO), Peroxiredoxin, and Ferric Reducing Ability of Plasma (FRAP) levels in newly diagnosed patients with T2DM. Method: In this case-control study, we included 63 patients as cases (newly diagnosed T2DM patients) and 63 as controls (healthy individuals). Detailed clinic-demographic data were recorded for all participants. Furthermore, fasting and post-prandial plasma glucose, HbA1c, NO, FRAP and peroxiredoxin were calculated. Statistical analysis was conducted to compare the findings between the two groups. Results: The preponderance of cases and controls were aged between 61 and 65. Male patients were the majority in both groups. The majority of reported cases involved alcohol consumption (p=0.0314*). The study revealed significant differences in kidney function, lipid profile, fasting and postprandial plasma glucose, and Hba1c levels between cases and controls (p<0.05). NO and FRAP levels in the case group were significantly lower (p<0.0001*), while peroxiredoxin levels were significantly higher (p<0.0001*). Conclusion: T2DM is associated with increased oxidative stress, indicated by elevated levels of Peroxiredoxin and decreased levels of FRAP and NO. These alterations in antioxidant defence mechanisms may serve as early indicators for the development of T2DM complications.